Pengaruh Penjualan dan Debet To Equity Ratio terhadap Laba Bersih Perusahaan Retail yang terdaftar di BEI Periode 2012-2018 - Endah Dewi Purnamasari (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2019)
This study aims to determine the effect of Sales and Debt To Equity Ratio (DER) on earnings at retail companies on the IDX. The research period began in 2012-2018 in 10 retail companies. The type of data used is secondary data. The results of data processing for the F test can be seen in the table above. Prob value F (Statistic) of 0.004 is smaller than the 0.05 significance level so that it can be concluded that the estimated regression model is feasible to use to explain the effect of sales and DER on earnings. Based on the results of the t test the value of prob. t arithmetic from sales of 0.0015 which is smaller than 0.05 so that sales have a significant effect on earnings at 95% confidence level. Unlike the case with the effect of DER on earnings dependent variables because of the value of prob. t count 0.6248 which is greater than 0.05 so it can be said that DER has no effect on the dependent variable of earnings. Keyword: DER, Sales and Earnings.